Vacuolate-attached filaments: highly productive Ridgeia piscesae epibionts at the Juan de Fuca hydrothermal vents - Kalanetra, Karen M; Nelson, Douglas C (MARINE BIOLOGY, 2010)
Vacuolate sulfur bacteria with high morphological similarity to vacuolate-attached filaments previously described from shallow hydrothermal vents (White Point, CA) were found at deep-sea hydrothermal vents. These filamentous bacteria grow in dense mats that cover surfaces and potentially provide a significant source of organic carbon where they occur. Vacuolate-attached filaments were collected near vents at the Clam Bed site of the Endeavour Segment of the Juan de Fuca Ridge and from the sediment surface at Escanaba Trough on the Gorda Ridge. A phylogenetic analysis comparing their 16S rRNA gene sequences to those collected from the shallow White Point site showed that all vacuolate-attached filament sequences form a monophyletic group within the vacuolate sulfur-oxidizing bacteria clade in the gamma proteobacteria. Abundance of the attached filaments was quantified over the length of the exterior surface of the tubes of Ridgeia piscesae worms collected from the Clam Bed site at Juan de Fuca yielding a per worm average of 0.070 +/- A 0.018 cm(3) (n = 4). In agreement with previous results for White Point filaments, anion measurements by ion chromatography showed no detectable internal nitrate concentrations above ambient seawater (n = 9). For one R. piscesae tube worm ``bush{\{}''{\}} at the Easter Island vent site, potential gross epibiont productivity is estimated to be 15 to 45x the net productivity of the worms.
Keywords: HOV Alvin (Human Occupied Vehicle)